USING “THREE-STEP INTERVIEW” STRATEGY TO ENHANCE SPEAKING OF HORTATORY EXPOSITION TEXTS TO THE ELEVENTH GRADERS (RETAIN, 2017)
USING “THREE-STEP INTERVIEW” STRATEGY TO ENHANCE SPEAKING OF HORTATORY EXPOSITION TEXTS TO THE ELEVENTH GRADERS Kharisma Zahrotul Afdil Aini English Language Teaching, Language and Art Faculty, State University of Surabaya Kharisma.afdhil@gmail.com Abstract Speaking is the most essential skill compared to the other three skills (listening, reading, and writing) since it is used for oral communication. In line with the objective of the English Education in Indonesia, that is to enable learners to communicate orally and in written, hence, it is clear that the students in Indonesia have to be able to speak in English. Unfortunately, the fact shows that most students cannot speak English well even though they have learnt English for years and get excellent scores in their written exam. Many reasons actually underlie this phenomenon, but the most influential thing is the fact that teachers’ lack knowledge in using creative and innovative teaching strategy in teaching and using English to communicate in the classroom. Therefore, it is necessary to conduct a research related to the implementation of innovative teaching strategy to help students improve their speaking ability. Thus, this study aims to know whether the implementation of three step interview, may help learners improve their speaking ability, especially the speaking of hortatory exposition texts. The design of this study is an experimental quantitative research. The subjectsare the eleventh graders chosen by using cluster random sampling. The research instruments used are a pre-test and a post test. The data are in the form of students’ speaking pre-test and post-test scores which are analyzed by using t-test formula to find its significance. The result shows thatthree-step interview strategy could help learners improve their speaking ability since there is a significant difference between a group taught by using the strategy and the one which is not. The calculation of the t-value is 4.33 and the t-table is 2.02 with 44 degrees of freedom. In this case, the mean scores of the experimental group is higher than that of the control group, that is 82.06 and 71.39. In addition, the effect size given by the strategy is included into moderate effect with the result of etha square calculation of0.022. Keywords: Three-step Interview strategy, speaking ability, hortatory exposition texts Abstrak BerbicaraMerupakan kemampuan yang sangat penting jika dibandingkan dengan tiga kemampuan lainnya (mendengar, membaca, danmenulis) karenadigunakan sebagai alat komunikasi lisan. Sejalan dengan tujuan dari pendidikan BahasaInggris yakni agar siswa mampu berkomunikasi baik secara lisan maupun tulisan, oleh sebab itu jelas bahwa siswa di Indonesia harus mampu untuk berbicaradalamBahasaInggris. Tetapi, keadaan sesungguhnya menunjukkanbahwa kebanyakan siswa tidak mampu berbicara BahasaInggris dengan baik walaupunmerekamendapatkannilaimemuaskan di ujiantulisnya. Hal ini sesungguhnya terjadikarena beberapaalasan, tetapi hal yang paling berpengaruh pada siswa adalah karena kurangnya pengetahuan guru dalam menggunakan strategi yang inovatif dan kreatif dalam mengajar dan menggunakan BahasaInggris untuk berkomunikasi di dalamkelas. Oleh karenaitu, penting untuk melakukan penelitian terkaitdengan penggunaan strategi yang berinovasi untuk membantu siswa meningkatkan kemampuan berbicara mereka. Sehingga, penelitianinibertujuanuntuk mengetahui apakah penggunaan satu dari beberapa strategi yang berinovasi, yakni three step interview mungkin bisa membantu siswa untuk meningkatkan kemampuan berbicara mereka khususnya di dalam teks eksposisihortatori. Desainpenelitianiniadalahquantitatifeksperimen. Subjek dari penelitian ini adalah siswa kelas XI SMA yang dipilih dengan menggunakan cluster sampling. Instrumen penelitian yang digunakanadalah pre-test dan post-test. Setelahmendapatkan data-data yang diperlukan, kemudian data dianalisismenggunakanformula t-test untuk mengetahui signifikannya. Hasil dari penelitian ini menunjukkan bahwa strategi three-step interview dapat membantu siswa dalam meningkatkan kemampuan berbicara mereka dalam Bahasa Inggris karena ditemukan adanya perbedaan signifikan pada kelas yang diajar menggunakan strategi three-step interview dan kelas yang tidak diajar menggunakan strategi tersebut. Hasil perhitungan dari t-value adalah 4,33 dan t-table adalah 2.02 dengan df = 44. Dalam hal ini, skor rata-rata dari grub experimental lebih tinggi daripada skor rata-rata dari grub kontrol, yakni 82,06 dan 71,39. Sebagai informasi tambahan, efek yang diberikan oleh strategi three-step interview tergolong ke dalam efek sedang dengan hasil perhitungan etha square yakni 0,022. Kata kunci: StrategiThree-step Interview, kemampuanberbicara, tekseksposisihortatori